Structural dynamics and stability analysis of a novel ARSK variant confirms its role in MPS type X pathogenesis - Muhammad Bilal; Muhammad Fakhar; Thamir Eid; Nawal Helmi; Misbahuddin Rafeeq; Mehreen Gul; Hammal Khan; Muhammad Umair (Glycoconjugate Journal, 2026)

Ecosystem carbon stocks across mangrove stand ages and hydrogeomorphological settings in Indonesia - Aulia Rahim; Martin Zimmer; Muhammad Helmi; Jumari Jumari; Lukman Lukman; Tri Retnaningsih Soeprobowati (Continental Shelf Research, 2026)

Evaluation and bias correction of high-resolution satellite and reanalysis rainfall products across Egypt’s hydrological zones - Mahmoud Hesham; Ahmed M. Helmi; Mohamed Elkiki; Yasser Hamed; Tarek Selim (Theoretical and Applied Climatology, 2026)

Prophylactic esketamine for postoperative sore throat: a meta-analysis of randomized evidence - Youssef Heikal; Mohamed Wagdy; Ahmad Alkheder; Farah Al-Hasani; Leen Helmi Radwan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multi-seasonal rainfall patterns over Indonesian maritime continent derived from long-term IMERG V07B data and rain gauge observations - Ravidho Ramadhan; Marzuki Marzuki; Fredolin Tangang; Hiroyuki Hashiguchi; Helmi Yusnaini; Robi Muharsyah; Fajar Adi-Kusumo; Mutya Vonnisa; Hermansah Hermansah (Atmospheric Research, 2026)

Spatiotemporal analysis of mangrove cover change and future projections in West Sumatra and Northern Java - Aulia Rahim; Tri Retnaningsih Soeprobowati; Muhammad Helmi; Łukasz Kruszewski (Landscape and Ecological Engineering, 2026)

External validation of a US claims-based frailty indicator and development of a population-specific model for the German healthcare system - Nina Mielke; Damiano Ferrari; Muhammad Helmi Barghouth; Natalie Ebert; Janine Kaiser; Elke Schaeffner (GeroScience, 2026)
Frailty increases the risk of adverse outcomes in older adults and is an important target for preventive care. Clinical frailty measures are established but rarely available at scale due to limited functional data in routine healthcare records. Claims-based frailty prediction models offer a pragmatic approach for population-level risk stratification but are often developed in specific healthcare systems and lack external validation. We aimed to externally validate and recalibrate the Claims-Based-Frailty-Indicator (CFI) and develop a claims-based frailty model for the German healthcare context. We used data from the Berlin Initiative Study, a cohort of older adults with assessment of the frailty phenotype, linked to individual health insurance claims and cause-of-death data. External validation of CFI was assessed by discrimination and calibration. Additionally, a new claims-based frailty model was developed. Model performance and application were evaluated through associations with mortality and hospital admission. Reporting followed TRIPOD statement. Among 1,151 participants (mean age 84.4 years; 55% women), the CFI demonstrated good discrimination (AUC 0.78) but poor calibration; recalibration of intercept improved calibration. Maximizing the Youden Index identified an optimal frailty threshold corresponding to a predicted probability of 0.39. The new model showed improved discrimination (AUC 0.82). Predicted frailty was similarly associated with mortality and hospital admissions as the frailty phenotype. Claims-based frailty models can be validated, recalibrated, and adapted to the German healthcare system. They provide a feasible approach for population-level frailty assessment and may support health services research, risk stratification, and care planning for older adults.

Unveiling Complete Genome of Streptococcus agalactiae from Malaysian Aquaculture: A Closer Look at Molecular Characteristics and Phylogenomic - Helmi Husaini Zainal Fithri; Nurul Hidayah Samsulrizal; Nur-Nazifah Mansor; Nurasyikin Hamzah; Noor Hanis Abu Halim; Mohd Syafiq Mohammad Ridzuan; Azila Abdullah; Nur Amalin Sofea Abdul Rahim; Azzmer Azzar Abdul Hamid (Marine Biotechnology, 2026)

Improving mechanical and physical properties of citric acid-bonded kenaf particleboard with gelatinized starch - Rusydi Aiman Ramli; Wei Chen Lum; Yusri Helmi Muhammad; Siti Noorbaini Sarmin; Muhammad Firdaus Zamin; Widya Fatriasari; Apri Heri Iswanto; Seng Hua Lee (Journal of the Indian Academy of Wood Science, 2026)

Human development under environmental and socioeconomic pressures: an ARDL-based assessment of life expectancy in Pakistan - Muhammad Khalid Anser; Muhammad Imran; Helmi Ali Mkaouar; Jameel Ahmad Khader; Alaa Shoukry; Wasfi Yengui; Kamran Azam; Khalid Zaman (Air Quality, Atmosphere & Health, 2026)

Convolutional Neural Networks Optimized for Land Cover Mapping in the Iraqi Province of Al-Muthanna’s Al-Khidhir Region - Yasir Abdulameer Nayyef Aldabbagh; Helmi Zulhaidi Mohd Shafri; Shattri Mansor; Mohd Hasmadi Ismail (Journal of the Indian Society of Remote Sensing, 2026)

Cloud-based assessment of aerosol dynamics and population exposure in Southeast Asia using MERRA-2 and AERONET integration - Zhi Zheng; Helmi Zulhaidi Mohd Shafri; Dong Wei; Pengfei Jia; Shengrui Yu; Kailin Zhu; Abdul Rashid Mohamed Shariff (Atmospheric Environment, 2026)

Anti-Photoaging Activity of a Structurally Optimized Curcumin Analogue (THHGV-5) in UV-B-Irradiated Human Dermal Fibroblasts: An Integrated In Silico and In Vitro Study - Retno MURWANTI; Vigha Ilmanafi ARIFKA; Rosalina Diani Prima ANARGYA; Prajona MARBUN; Aisyah Nur DAMAYANTI; Agus SYAHPUTRA; Helmi Hana PRINANDA; Ritmaleni RITMALENI (Cell Biochemistry and Biophysics, 2026)

Pioneering sustainable governance reporting: A novel governance-life cycle assessment framework - Seok Peng Ngan; Sue Lin Ngan; DongHui Zhao; Puan Yatim; Mohd Helmi Ali; Hon Loong Lam (Sustainable Production and Consumption, 2026)

Development of novel GABA-fortified fermented milk using probiotic Lactiplantibacillus plantarum B7 immobilised on natural supports - Sangkaran Pannerchelvan; Helmi Wasoh; Mohamad Zulfazli Mohd Sobri; Mohd Shamzi Mohamed; Fadzlie Wong Faizal Wong; Rosfarizan Mohamad; Mohammad Rizal Kapri; Murni Halim (Systems Microbiology and Biomanufacturing, 2026)

Heavy Metal Air Pollution: Human Health Effects and Nanomaterial Strategies for Monitoring and Remediation - Yosri A. Fahim; Haneen M. Boughdady; Walid A. Othman; Sondos M. Mostafa; Lara M. Helmi; Ahmed A. Elsayed; Omar S. Hamouda; Osama M. Gad; Reem M. Sallam (Biological Trace Element Research, 2026)

Circularity assessment of power electronic converters: manual disassembly, bill of material, circularity indicators and actionable guidelines - Irati Ruiz de Azua Lahidalga; Christian Wandji; Aitor Picatoste; Daniel Justel; Iosu Aizpuru; Andreas Riel; Helmi Ben Rejeb; Joan Manuel F. Mendoza (Journal of Cleaner Production, 2026)

Active fault map and paleoseismology results from the Aceh Fault in North Sumatra, Indonesia: Unravelling faulting dynamics along the Great Sumatran Fault system - Gayatri Indah Marliyani; Yann Klinger; Aulia Kurnia Hady; Agung Setianto; Wenqian Yao; Hurien Helmi; Telly Kurniawan; Retno Agung Prasetyo Kambali; Zulham Sugito; Abdi Jihad; Yosi Setiawan; Andi Azhar Rusdin; et al. (Tectonophysics, 2026)

Future projections of extreme precipitation over Indonesia's new capital under climate change scenario using CORDEX-SEA regional climate models - Marzuki Marzuki; Ravidho Ramadhan; Helmi Yusnaini; Liew Juneng; Fredolin Tangang; Mutya Vonnisa; Afdal Afdal; Muhammad Rais Abdillah; Rahmat Hidayat (Atmospheric Research, 2026)

Environmental monitoring and bioassessment of schoolchildren’s exposure to lead and cadmium from industrial pollution - Helmi E.; Araoud M.; Nouioui M.A.; Taieb D.; Bardi H.; Nacef T.; Hedhili A. (Environmental Monitoring and Assessment, 2025)

Mangrove landscape dynamics and ecosystem services sustainability in the coral triangle Southeast Sulawesi, Indonesia - Kangkuso Analuddin; Saban Rahim; Raden Marsuki Iswandi; Weka Widayati; Wa Iba; Laode Muhammad Golok Jaya; Andi Septiana; Muhammad Helmi; Rudhi Pribadi; Luky Adriyanto; Takashi Nakamura; Kazuo Nadaoka (Regional Studies in Marine Science, 2025)

Spatial distribution of extreme upwelling event in the Seas of Alor Kecil, Indonesia, revealed by UAV’s thermal infrared sensor - Anindya Wirasatriya; Sigit Bayhu Iryanthony; R. Dwi Susanto; Teguh Agustiadi; Kunarso; Aris Ismanto; Muhammad Helmi; Muhammad Zainuri; Rikha Widiaratih; Gentio Harsono; Dwiyoga Nugroho; Adi Purwandana; et al. (Regional Studies in Marine Science, 2025)

Fiscal monitoring policy and corporate carbon emissions in U.S firms - Mohamed Shaker Ahmed; Elie Bouri; Charilaos Mertzanis; Mohamad Husam Helmi (Journal of Environmental Management, 2025)

Advances in catalysis for biodiesel production: Integrating AI-driven optimization and bibliometric insights into renewable energy technologies - Nur Fatin Sulaiman; Saraswathy Shamini Gunasekaran; Halimah Badioze Zaman; Siti Nur Ashakirin Mohd Nashruddin; Siti Nur Aida Mohd Nashruddin; A.G.N. Sofiah; Mohamad Helmi Abd Mubin; Siew Ling Lee (Bioresource Technology, 2025)

Functional role of Dictyota dichotoma extract in mitigating heat stress adverse effects and enhancing physiological resilience in growing rabbits - Mohamed G. E. Metwally; Fatima S. Alaryani; Fatima A. Jaber; Reem Hasaballah Alhasani; Dalia M. Alammari; Nawal Helmi; Garsa Alshehry; Sameh A. Abdelnour; Laila B. Bahgat; Mohammed A. E. Naiel (Tropical Animal Health and Production, 2025)

Long‐Term Spatial–Temporal Variability, Trends and Extreme Rainfall Events Over Indonesia Based on 43 Years of CHIRPS Data - Marzuki Marzuki; Ravidho Ramadhan; Helmi Yusnaini; Mutya Vonnisa; Robi Muharsyah; Yudha Nugraha; Anna Yunita Sari; Aisyah Erajalita (International Journal of Climatology, 2025)
Understanding rainfall variability and trends across Indonesia is crucial for developing strategies to mitigate the impacts of climate change. This study examines the spatial–temporal variability and trends in rainfall across Indonesia using long‐term (1981–2023) Climate Hazards Group InfraRed Precipitation with Stations (CHIRPS) v2.0 data. Rainfall variability was quantified using monthly and daily rainfall indices, while trends were examined with the Mann–Kendall test and the Theil–Sen method. Evaluation against 67 rain gauge stations showed high reliability of CHIRPS v2.0 data (CC > 0.7; RB 20 mm/year, p

Diurnal Rainfall Variability in Kalimantan: Insights From Precipitation Amount, Frequency, Intensity, and Duration - Anna Y. Sari; Marzuki Marzuki; Helmi Yusnaini; Ravidho Ramadhan; Robi Muharsyah (International Journal of Climatology, 2025)
This study examined the diurnal variation in rainfall in Kalimantan, focusing on precipitation accumulation (PA), precipitation frequency (PF), and precipitation intensity (PI), using rain gauge data from 103 stations (2016–2022) and Integrated Multi‐Satellite Retrievals for Global Precipitation Measurement Version 07 B (IMERG V07B) for an extended period (2002–2022). The results showed that PA was more closely aligned with PF than with PI, indicating that PF played a dominant role in determining total precipitation across Kalimantan. Diurnal peaks of PA and PF were observed in coastal regions during the late afternoon to early evening (14–19 local standard hours [LST]), whereas inland and mountainous regions experienced these peaks in the early morning (00–03 LST). In contrast, PI exhibited greater spatial and temporal variability, reflecting the influence of localised convective processes. Cluster analysis of PA, PF, and PI identified four distinct regions based on peak time and amplitude, showing a strong dependence on topographic features and distance from the coastline. Short‐duration rainfall events ( 6 h) tended to dominate in inland flat regions, although they were still occasionally observed in mountainous areas during the early morning hours. These patterns were driven by onshore rainfall propagation, as observed in the IMERG time cross‐sections, where rainfall moved inland from the southwestern coast between 18 and 00 LST and persisted over mountainous areas for 1–3 h before propagating northeastward between 03 and 08 LST. Offshore propagation observed in the northwest and southeast regions of Kalimantan between 00 and 06 LST further highlights the role of low‐level wind patterns and local atmospheric convergence in modulating rainfall distribution. This study enhances our understanding of the complex diurnal rainfall patterns in Kalimantan.

Influence of Madden-Julian Oscillation on diurnal precipitation dynamics in the Mentawai Islands: A high-resolution satellite perspective - Aisyah Erajalita; Marzuki Marzuki; Helmi Yusnaini; Ravidho Ramadhan; Mutya Vonnisa (Atmospheric Research, 2025)

Multi-functional CaO@GO catalyst and adsorbent derived from eggshell waste for removal of environmental pollutants - Maryam Helmi; Bentolhoda Chenarani; Ahad Ghaemi; Alireza Hemmati (Fuel, 2025)

Daytime napping in young athletes: a scoping review on prevalence, methodology, and effects on physical fitness and sport-specific performance - Sonia E. U. Schmidt; Monique Wochatz; Helmi Chaabene; Olaf Prieske (German Journal of Exercise and Sport Research, 2025)
Optimal recovery strategies are crucial measures to ensure high-level performance in athletes. In this context, short sleep breaks during the day, referred to as daytime napping, appear to be an effective means for enhancing performance. However, high-level evidence (e.g., systematic reviews, meta-analyses) on the methods and effects of daytime napping on physical fitness and/or sport-specific performance is currently limited to adults in competitive sport. The aim of the present scoping review was to investigate the prevalence rates, methods, and effects of daytime napping in young athletes. For this purpose, a systematic literature analysis of scientific databases (Medline, Web of Science) was performed between September 2023 and March 2024. Studies were included that examined healthy young athletes with a mean age of 6–19 years, focusing on napping behavior and/or the effects of daytime napping on physical fitness/sport-specific performance parameters. Our literature search resulted in 12 studies with a total of 1186 young athletes. Results indicated that the prevalence rate of daytime napping in young athletes ranged between 37% and 91%. Most napping approaches comprised frequencies of one to two power naps per week, lasting 30–60 min/nap, typically in the early afternoon (12:00–16:00). Small-to-large increases in reaction time tests were observed as a result of daytime napping. The effects on other fitness parameters (e.g., speed, power) or sport-specific performance (e.g., shooting) were less consistent. In summary, the data on napping characteristics and napping effects suggested that naps in young athletes should last approximately 30–60 min, occur in the afternoon (12:00–16:00), and should be separated by at least 30 min between napping and fitness testing. Research gaps that were identified include studies focusing on puberal athletes, sex-specific analyses, controlled longitudinal study design, and protocols addressing moderator variables such as time of day and/or the time interval between napping and performance testing.

Harnessing artificial neural networks for coastal erosion prediction: A systematic review - Abdul Rehman Khan; Mohd Shahrizal Bin Ab Razak; Badronnisa Binti Yusuf; Helmi Zulhaidi Bin Mohd Shafri; Noorasiah Binti Mohamad (Marine Policy, 2025)

Cytotoxic and anti-migration effects of cardiac glycosides from Gomphocarpus fruticosus and Kanahia laniflora on hepatocellular carcinoma; LC-MS/MS profiling, in vitro bioassay and molecular docking study - Helmi A. Mokbel; Seham S. El Hawary; Rasha M. Allam; Ahmed H. Eldesoky; Ali M. El-Halawany; Amira K. El-Motayam (South African Journal of Botany, 2025)

Advancements in transesterification of waste cooking oil to biodiesel using rare earth metal oxide catalysts: A bibliometric analysis and future prospects - Nur Fatin Sulaiman; Saraswathy Shamini Gunasekaran; Siti Nur Ashakirin Mohd Nashruddin; Siti Nur Aida Mohd Nashruddin; A.G.N. Sofiah; Mohamad Helmi Abd Mubin; Siew Ling Lee (Fuel, 2025)

Recent advancements in the treatments of the organic fraction of municipal solid waste towards circular economy - N. A. N. Md Nasir; I. A. Zakarya; N. Anuar; S. A. Kamaruddin; N. A. M. Helmi (International Journal of Environmental Science and Technology, 2025)

Circular supply chain in Industry 4.0: Improving resource management and addressing recycling challenges - Ming-Lang Tseng; Mohd Helmi Ali; Shulin Lan; Anthony S.F. Chiu (Resources, Conservation and Recycling, 2025)

Posterior saibo selection in the Japanese pearl oyster, Pinctada fucata martensii, as a non-genetic approach to producing high-quality cultured pearls - Suzuka Yamaoka; Gunawan Muhammad; Muhammad Helmi Fauzan; Asep Sahidin; Akira Komaru (Aquaculture International, 2025)

Site-specific nutrient management for rice using soil properties to adjust phosphorus and potassium supply from compound NPK fertilizer - Setia Sari Girsang; Rowena L. Castillo; Mahyuddin Syam; Zulkifli Zaini; Sunendar Kartaatmadja; Suyamto; Judith Carla Dela Torre; Irish Lorraine B. Pabuayon; Romalene A. Limpiada; Waluyo; Helmi; Samijan; et al. (Field Crops Research, 2025)

Behavior of Cloud Base Height over Sumatra Mountains Region from Ceilometer Observations - Helmi Yusnaini; Marzuki Marzuki; Hiroyuki Hashiguchi; Ravidho Ramadhan; Elfira Saufina (Atmospheric Research, 2025)

Evaluation of methoxyflavones as dengue NS2B–NS3 protease inhibitors: an in silico and in vitro studies - Nur Farhana Mustafa; Kian-Kai Cheng; Siti Aisyah Razali; Habibah A. Wahab; Nurul Hanim Salin; Iffah Izzati Zakaria; Muhammad Helmi Nadri (Molecular Diversity, 2025)

Mapping the interplay of technical, economic, social, and environmental dimensions in food-sector wastewater reclamation: A systematic literature review - Nabiilah Mat Yusoff; Norhidayah Suleiman; Asma-Qamaliah Abdul-Hamid; Mohd Helmi Ali (Journal of Environmental Management, 2025)

Dengue fever prediction using LSTM and integrated temporal-spatial attention: a case study of Malaysia - Mokhalad A. Majeed; Helmi Z. M. Shafri; Zed Zulkafli; Aimrun Wayayok (Spatial Information Research, 2025)

Maximizing circular economy benefits for manufacturing companies: A simulation tool for defining and implementing a circular product strategy - Christian Wandji; Andreas Riel; Helmi Ben Rejeb; Mohammad Kanso; Florent Pitis (Sustainable Production and Consumption, 2025)

Sustainable urban digital innovation: A socio-technical competency-based approach to evaluation - Ahmad Helmi; Viviana Bastidas; Kwadwo Oti-Sarpong; Jennifer Schooling (Sustainable Cities and Society, 2024)

Characterizing the dynamics of climate and native desert plants in Qatar - Meshal Abdullah; Ammar Abulibdeh; Sophia Ghanimeh; Helmi Hamdi; Hezam Al- Awah; Talal Al-Awadhi; Midhun Mohan; Zahraa Al-Ali; Abdullah Sukkar; Ahmed M. El Kenawy (Journal of Arid Environments, 2024)

Culture-based and molecular investigation of antibiotic and metal resistance in a semi-arid agricultural soil repeatedly amended with urban sewage sludge - Sonia Mokni-Tlili; Anna Markowicz; Sławomir Sułowicz; Helmi Hamdi (Environmental Research, 2024)

Improvement of ɣ-Aminobutyric Acid Production and Cell Viability of Lactiplantibacillus plantarum B7 via Whole-Cell Immobilisation in Repeated Batch Fermentation System - Sangkaran Pannerchelvan; Faris Nulhaqim Muhamad; Helmi Wasoh; Mohd Shamzi Mohamed; Fadzlie Wong Faizal Wong; Rosfarizan Mohamad; Murni Halim (Probiotics and Antimicrobial Proteins, 2024)

Land-sea contrast of vertical structure of precipitation over Sumatra revealed by GPM DPR observations - Helmi Yusnaini; Marzuki Marzuki; Ravidho Ramadhan; Rahmat Ilham; Mutya Vonnisa; Hiroyuki Hashiguchi (Atmospheric Research, 2024)

Cross-sectional study of the association of respiratory diseases health risk with environmental pollutants and climate change in Saudi Arabia - Maryam A. Al-Ghamdi; Nawal Helmi; Said S. Moselhy (Environmental Science and Pollution Research, 2024)

Trajectory of microplastic particles with 2-dimensional hydrodynamic modelling approach at Pekalongan waters, Central Java, Indonesia - Malya Asoka Anindita; Aris Ismanto; Muhammad Zainuri; Tony Hadibarata; Kunarso Kunarso; Lilik Maslukah; Sugeng Widada; Elis Indrayanti; Rikha Widiaratih; Denny Nugroho Sugianto; Baskoro Rochaddi; Muhammad Helmi; et al. (Environmental Monitoring and Assessment, 2024)

A Comparative Analysis Assessing Growth Dynamics of Locally Isolated Chlorella sorokiniana and Chlorella vulgaris for Biomass and Lipid Production with Biodiesel Potential - Hizbullahi Muhammad Usman; Mohd Farizal Kamaroddin; Mohd Helmi Sani; Nik A.N.N. Malek; Armstrong Ighodalo Omoregie; Afifi Zainal (Bioresource Technology, 2024)

Regulatory effect of Balanites aegyptiaca ethanol extract on oxidant/antioxidant status, inflammatory cytokines, and cell apoptosis gene expression in goat abomasum experimentally infected with Haemonchus Contortus - Doaa Sedky; Tamer Helmi Abd El-Aziz; Soad Mohamed Nasr; Sekena Hassanien Abdel-Aziem; Noha Mahmoud Fahmy Hassan; Amira Hassan Mohamed; Hala Abdalla Ahmed Abou Zeina (Tropical Animal Health and Production, 2024)
This experiment aimed to assess the regulatory effects of treatment with Balanites aegyptiaca fruit ethanol extract (BA-EE) on oxidant/antioxidant status, anti-inflammatory cytokines, and cell apoptosis gene expression in the abomasum of Haemonchus contortus –infected goats. Twenty goat kids were assigned randomly to four equal groups: (G1) infected-untreated, (G2) uninfected-BA-EE-treated, (G3) infected-albendazole-treated, (G4) infected-BA-EE-treated. Each goat in (G1), (G3), and (G4) was orally infected with 10,000 infective third-stage larvae. In the fifth week postinfection, single doses of albendazole (5 mg/kg.BW) and BA-EE (9 g/kg.BW) were given orally. In the ninth week postinfection, the animals were slaughtered to obtain abomasum specimens. The following oxidant/antioxidant markers were determined: malondialdehyde (MDA), glutathione (GSH), glutathione-S-transferase (GST), superoxide dismutase (SOD), catalase (CAT). The mRNA gene expression of cytokines (IL-3, IL-6, IL-10, TNF-α) and cell apoptosis markers (Bax, Bcl-2) were estimated. (G1) showed significantly reduced GSH content and GST and SOD activities but a markedly increased MDA level. (G3) and (G4) revealed a markedly lower MDA level with pronouncedly elevated GSH, SOD, and GST levels. The antioxidant properties of BA-EE were superior to those of albendazole. The mRNA gene expressions of IL-3, IL-6, IL-10, TNF-α, and Bax-2 were upregulated in (G1) but downregulated in (G3) and (G4). Bcl-2 and Bcl-2/Bax ratio expression followed a reverse course in the infected and both treated groups. We conclude that BA-EE treatment has a protective role in the abomasum of H. contortus –infected goats. This could be attributed to its antioxidant properties and ability to reduce pro-inflammatory cytokines and cell apoptosis.

Unveiling and modelling: Land degradation, poverty nexus in Nigeria's semi-arid (jigawa state) using cloud-based geospatial data - Jibrin Gambo; Siti Nur Aliaa Binti Roslan; Helmi Zulhaidi Mohd Shafri; Nik Norasma Che Ya; Yusuf Ahmed Yusuf (Journal of Arid Environments, 2024)

Black carbon instrument responses to laboratory generated particles - Laura Salo; Karri Saarnio; Sanna Saarikoski; Kimmo Teinilä; Luis M.F. Barreira; Petteri Marjanen; Sampsa Martikainen; Helmi Keskinen; Katja Mustonen; Teemu Lepistö; Päivi Aakko-Saksa; Henri Hakkarainen; et al. (Atmospheric Pollution Research, 2024)

Normative Values for Measures of Physical Fitness Among Tunisian School Children - Yassine Negra; Senda Sammoud; Tony Myers; Alan Michael Nevill; Helmi Chaabene (Journal of Science in Sport and Exercise, 2024)

Transformer-based semantic segmentation for large-scale building footprint extraction from very-high resolution satellite images - Mohamed Barakat A. Gibril; Rami Al-Ruzouq; Abdallah Shanableh; Ratiranjan Jena; Jan Bolcek; Helmi Zulhaidi Mohd Shafri; Omid Ghorbanzadeh (Advances in Space Research, 2024)

Large-scale assessment of date palm plantations based on UAV remote sensing and multiscale vision transformer - Mohamed Barakat A. Gibril; Helmi Zulhaidi Mohd Shafri; Abdallah Shanableh; Rami Al-Ruzouq; Shaiful Jahari bin Hashim; Aimrun Wayayok; Mourtadha Sarhan Sachit (Remote Sensing Applications: Society and Environment, 2024)

Validating IMERG data for diurnal rainfall analysis across the Indonesian maritime continent using gauge observations - Ravidho Ramadhan; Marzuki Marzuki; Wiwit Suryanto; Sholihun Sholihun; Helmi Yusnaini; Robi Muharsyah (Remote Sensing Applications: Society and Environment, 2024)

Future prediction of coastal recession using convolutional neural network - Abdul Rehman Khan; Mohd Shahrizal Bin Ab Razak; Badronnisa Binti Yusuf; Helmi Zulhaidi Bin Mohd Shafri; Noorasiah Binti Mohamad (Estuarine, Coastal and Shelf Science, 2024)

Diurnal cycle of precipitation over coastal sea and small islands in the eastern region of Sumatra including season and Madden Julian Oscillation signatures - Marzuki Marzuki; Helmi Yusnaini; Ravidho Ramadhan; Robi Muharsyah; Mutya Vonnisa; Harmadi Harmadi; Fredolin Tangang (Atmospheric Research, 2024)

Rhamnolipids production by Pseudomonas aeruginosa RW9 using palm oil mill effluent sludge oil as a carbon source - Nur Aina Natasha Mohd Asmadi; Kar Mun Zee; Shobanah Menon Baskaran; Hidayah Ariffin; Helmi Wasoh; Toshinari Maeda; Mohd Ali Hassan; Mohd Rafein Zakaria (Biocatalysis and Agricultural Biotechnology, 2024)

Mitigating soil water deficit using organic waste compost and commercial water retainer: a comparative study under semiarid conditions - Hatem Zgallai; Rahma Inès Zoghlami; Mohamed Annabi; Olfa Zarrouk; Salah Jellali; Helmi Hamdi (Euro-Mediterranean Journal for Environmental Integration, 2024)
Semiarid regions have particularly been confronted with climate change effects reflected by the consistent decrease of rainfall and increase of evapotranspiration. This drought stress constitutes the main constraint for agricultural production improvement, which is aggravated by the fact that strategic (field) crops are mostly grown under rainfed systems. Therefore, the objective of this field study was to improve soil water retention by the application of two conditioners namely, an organic waste compost (DS) and a synthetic water-retaining hydrogel (WS). These amendments were applied to an agricultural soil for the cultivation of fodder maize under normal and deficit irrigation regimes. Advanced analysis showed a general disruption of plant growth parameters under water stress. However, both amendments attenuated this negative effect with respect to control by improving soil water status. More precisely, the measured soil water tension at the start of the dry season was the lowest in presence of DS (48 centibars), followed by WS (61 centibars), then unamended soil (83 centibars). Besides, compost application resulted in higher moisture (13.3%), nitrogen (0.36%), and organic matter (0.56%) in soil than the synthetic hydrogel at the end of the field experiment. Soil and plant characterization highlighted the combined effect of water deficit and conditioner type. Indeed, the consistent increase of soil water content in the presence of DS and WS improved all the addressed plant parameters when compared with untreated soil. Infrared thermal imaging showed that canopy temperature was lower in presence of both amendments while dry biomass yield increased by 38% when water supply was limited. Nevertheless, the long-term sustainability of the soil system appears to be better maintained in the presence of the organic waste compost. The latter has the added advantage of improving soil fertility in contrast to inert polymers.

Use of waste marble powder for the synthesis of novel calcium-rich biochar: Characterization and application for phosphorus recovery in continuous stirring tank reactors - Salah Jellali; Besma Khiari; Maram Al-Balushi; Jamal Al-Sabahi; Helmi Hamdi; Zohra Bengharez; Mohammed Al-Abri; Hamed Al-Nadabi; Mejdi Jeguirim (Journal of Environmental Management, 2024)

Unveiling groundwater potential zones as catalyst for multidimensional poverty reduction using analytical hierarchical process and geospatial decision support systems (S-DSS) approach in the semiarid region, Jigawa, Nigeria - Jibrin Gambo; Siti Nur Aliaa binti Roslan; Helmi Zulhaidi Mohd Shafrib; Nik Norasma Che Ya; Yusuf Ahmed Yusuf (Groundwater for Sustainable Development, 2024)

Influences of straw alkaline pretreatment on biogas production and digestate characteristics: artificial neural network and multivariate statistical techniques - Raid Alrowais; Noha Said; Mohamed Mahmoud-Aly; Ahmed M. Helmi; Basheer M. Nasef; Mahmoud M. Abdel daiem (Environmental Science and Pollution Research, 2024)

Prediction of extreme rain in Kototabang using Himawari-8 satellite based on differences in cloud brightness temperature - Nining Jumianti; Marzuki Marzuki; Helmi Yusnaini; Ravidho Ramadhan; Wendi Harjupa; Elfira Saufina; Fadli Nauval; Risyanto Risyanto; Anjar Dimara Sakti; Muhammad Rais Abdillah; Prasanti Widyasih Sarli (Remote Sensing Applications: Society and Environment, 2024)

Bridging the sustainable circular economy in cosmetic cross-supply chain practices under uncertainties: A data-driven influential model - Kuo-Jui Wu; Min Fu; Mohd Helmi Ali; Ming K. Lim; Ming-Lang Tseng (Journal of Cleaner Production, 2024)

Machine learning approach for core permeability prediction from well logs in Sandstone Reservoir, Mediterranean Sea, Egypt - Ali Mahdy; Wael Zakaria; Ahmed Helmi; Ahmad Sobhy Helaly; Abdullah M.E. Mahmoud (Journal of Applied Geophysics, 2024)

An integrated satellite characterization and hydrodynamic study in assessing coastal dynamics in Cirebon, West Java - Karlina Triana; Tubagus Solihuddin; Semeidi Husrin; Johan Risandi; Eva Mustikasari; Terry Louise Kepel; Hadiwijaya Lesmana Salim; Nasir Sudirman; Akhmad Tri Prasetyo; Muhammad Helmi (Regional Studies in Marine Science, 2023)

Recycling of gas-to-liquid sludge as a potential organic amendment: Effect on soil and cotton properties under hyperarid conditions - Oumaima Mabrouk; Helmi Hamdi; Sami Sayadi; Mohammad A. Al-Ghouti; Mohammed Abu-Dieyeh; Reginald Kogbara; Ali Al-Sharshani; Osman Abdalla; Sabah Solim; Nabil Zouari (Journal of Environmental Management, 2023)

Acute toxicity of palm oil mill effluent on zebrafish (Danio rerio Hamilton-Buchanan, 1822): Growth performance, behavioral responses and histopathological lesions - Ilham Zulfahmi; Sayyid Afdhal El Rahimi; Saed Dedi Suherman; Almunawarah Almunawarah; Arif Sardi; Kamaliah Helmi; Badratun Nafis; Adli Waliul Perdana; Khalisah Huwaina Adani; Ihdina Alfi Admaja Nasution; Kizar Ahmed Sumon; Mohammad Mahmudur Rahman (Chemosphere, 2023)

Biodiesel production from Mastic oil via electrolytic transesterification: optimization using response surface methodology and engine test - Maryam Helmi; Mohammad Amin Sobati; Alireza Hemmati (Environmental Science and Pollution Research, 2023)

Modular smart grid intelligence: Replicable concept for diverse scenarios - Ahmed M. Helmi; Haitham S. Ramadan; Abdoulkader I. Idriss (Sustainable Cities and Society, 2023)

Acute effects of concurrent muscle power and sport-specific endurance exercises on markers of immunological stress response and measures of muscular fitness in highly trained youth male athletes - Adrian Markov; Jens Bussweiler; Norman Helm; Fabian Arntz; Thomas Steidten; Lars Krohm; Arnau Sacot; Philipp Baumert; Christian Puta; Helmi Chaabene (European Journal of Applied Physiology, 2023)
Purpose To examine the acute effects of concurrent muscle power and sport-specific endurance exercises order on immunological stress responses, muscular-fitness, and rating-of-perceived-exertion (RPE) in highly trained youth male judo athletes. Methods Twenty male participants randomly performed two concurrent training (CT) sessions; power-endurance and endurance-power. Measures of immune response (e.g., white blood cells), muscular-fitness (i.e., counter-movement-jump [CMJ]), RPE, blood-lactate, and -glucose were taken at different time-point (i.e., pre, mid, post, and post6h). Results There were significant time*order interactions for white blood cells, lymphocytes, granulocytes, granulocyte-lymphocyte-ratio, and systemic-inflammation-index. Power-endurance resulted in significantly larger pre-to-post increases in white blood cells and lymphocytes while endurance-power resulted in significantly larger pre-to-post increases in the granulocyte-lymphocyte-ratio and systemic-inflammation-index. Likewise, significantly larger pre-to-post6h white blood cells and granulocytes increases were observed following power-endurance compared to endurance-power. Moreover, there was a significant time*order interaction for blood-glucose and -lactate. Following endurance-power, blood-lactate and -glucose increased from pre-to-mid but not from pre-to-post. Meanwhile, in power-endurance blood-lactate and -glucose increased from pre-to-post but not from pre-to-mid. A significant time*order interaction was observed for CMJ-force with larger pre-to-post decreases in endurance-power compared to power-endurance. Further, CMJ-power showed larger pre-to-mid performance decreases following power-endurance, compared to endurance-power. Regarding RPE, significant time*order interactions were noted with larger pre-to-mid values following endurance-power and larger pre-to-post values following power-endurance. Conclusion CT induced acute and delayed order-dependent immune cell count alterations in highly trained youth male judo athletes. In general, power-endurance induced higher acute and delayed immunological stress responses compared to endurance-power. CMJ-force and RPE fluctuated during both CT sessions but went back to baseline 6 h post-exercise.

Developing a hierarchical framework for assessing the strategic effectiveness of sustainable waste management in the Somaliland construction industry - Yeneneh Tamirat Negash; Abdiqani Muse Hassan; Ming-Lang Tseng; Mohd Helmi Ali; Ming K. Lim (Environmental Science and Pollution Research, 2023)

Synthesis, characterization and performance evaluation of NaOH@Chitosan-Fe3O4 as an adsorbent for CO2 capture - Maryam Helmi; Farzad Moazami; Ahad Ghaemi; Alireza Hemmati (Fuel, 2023)

Differentiation of lard from other animal fats based on n-Alkane profiles using chemometric analysis - Nur Ain Syaqirah Sapian; Muhamad Aidilfitri Mohamad Roslan; Amalia Mohd Hashim; Mohd Nasir Mohd Desa; Murni Halim; Yanty Noorzianna Abdul Manaf; Helmi Wasoh (Food Research International, 2023)

Can cheniers protect mangroves along eroding coastlines? – The effect of contrasting foreshore types on mangrove stability - Celine E.J. van Bijsterveldt; Daphne van der Wal; Alejandra Gijón Mancheño; Gregory S. Fivash; Muhammad Helmi; Tjeerd J. Bouma (Ecological Engineering, 2023)

Serum Levels of Growth-Associated Protein-43 and Neurotrophin-3 in Childhood Epilepsy and Their Relation to Zinc Levels - Ali Helmi Bakri; Mohammed H. Hassan; Ahmed El-Abd Ahmed; Ghallab Alotaibi; Pola Rafat Halim; Ahmed Alamir Mahmoud Abdallah; Nagwan I. Rashwan (Biological Trace Element Research, 2023)
Background Epilepsy is one of the most common neurological disorders, and it places a significant economic strain on the healthcare system around the world. Although the exact mechanism of epilepsy has yet to be illustrated, various pathogenic cascades involving neurotransmitters and trace elements have been reported. We aimed to investigate the serum levels of growth-associated protein-43 (GAP-43) and neurotrophin-3 (NT-3) among cohort of Egyptian children with epilepsy and correlate these biomarkers with their zinc levels. Methods This case–control study included 50 pediatric patients with epilepsy who were comparable with 50 controls. Neurological assessment and electroencephalogram (EEG) were done to all included children. Biochemical measurements of serum GAP-43 and NT-3 using enzyme linked immunosorbent assays (ELISA), and total antioxidant capacity (TAC) and zinc using colorimetric assays, were performed to all participants. Results There was significantly frequent positive parental consanguinity among cases with significantly frequent generalized onset seizures (94%) than simple partial seizure (6%). There were significantly lower serum GAP-43 and zinc levels with significantly higher TAC among cases vs. the controls, p ˂0.05 for all. There was no significant difference in the serum levels of NT-3 among epileptic children vs. the controls, p = 0.269. Serum Zn was positively correlated with GAP-43 level among epileptic children ( r = 0.381, p = 0.006). Serum GAP-43 in diagnosing childhood epilepsy at cut-off point ≤ 0.6 ng/mL showed 78% sensitivity, 62% specificity, positive predictive value ( PPV ) = 50.6%, negative predictive value ( NPP ) = 84.9% with AUC = 0.574. Conclusion GAP-43 can be considered a sensitive good negative biomarker in childhood epilepsy which correlated positively with the zinc status.

Seasonal variability of Total Suspended Sediment off the Banjir Kanal Barat River, Semarang, Indonesia estimated from Sentinel-2 images - Anindya Wirasatriya; Lilik Maslukah; Elis Indrayanti; Muh. Yusuf; Adzkia Pincta Milenia; Alvin Aulia Adam; Muhammad Helmi (Regional Studies in Marine Science, 2023)

Comparison of vertical profile of raindrop size distribution from micro rain radar with global precipitation measurement over Western Java Island - Marzuki Marzuki; Ravidho Ramadhan; Helmi Yusnaini; Findy Renggono; Mutya Vonnisa; Hiroyuki Hashiguchi (Remote Sensing Applications: Society and Environment, 2023)

Understanding barriers and motivations in solid waste management from Malaysian industries: a comparative analysis - Mansoor Ahmed Soomro; Mohd Helmi Ali; Suhaiza Zailani; Ming-Lang Tseng; Zafir Mohd Makhbul (Environmental Science and Pollution Research, 2023)

Symmetric and asymmetric impacts of the palm oil industry on carbon dioxide emissions in Malaysia based on linear and nonlinear autoregressive distributed lag models - Norlin Khalid; Mohd Helmi Ali; Nur Hilfa Awatif Mohamad Ridzuan; Ming-Lang Tseng; Mohd Shahrul Mohd Nadzir; Shifa Md Nor (Clean Technologies and Environmental Policy, 2023)

Oil palm yield prediction across blocks from multi-source data using machine learning and deep learning - Yuhao Ang; Helmi Zulhaidi Mohd Shafri; Yang Ping Lee; Shahrul Azman Bakar; Haryati Abidin; Mohd Umar Ubaydah Mohd Junaidi; Shaiful Jahari Hashim; Nik Norasma Che’Ya; Mohd Roshdi Hassan; Hwee San Lim; Rosni Abdullah; Yusri Yusup; et al. (Earth Science Informatics, 2022)

Co-occurrence of antibiotic and metal resistance in long-term sewage sludge-amended soils: influence of application rates and pedo-climatic conditions - Sonia Mokni-Tlili; Sarra Hechmi; Hadda-Imene Ouzari; Najet Mechergui; Manel Ghorbel; Naceur Jedidi; Abdennaceur Hassen; Helmi Hamdi (Environmental Science and Pollution Research, 2022)
Urban sewage sludge (USS) is increasingly being used as an alternative organic amendment in agriculture. Because USS originates mostly from human excreta, partially metabolized pharmaceuticals have also been considered in risk assessment studies after reuse. In this regard, we investigated the cumulative effect of five annual USS applications on the spread of antibiotic-resistant bacteria (ARB) and their subsequent resistance to toxic metals in two unvegetated soils. Eventually, USS contained bacterial strains resistant to all addressed antibiotics with indices of resistance varying between 0.25 for gentamicin to 38% for ampicillin and azithromycin. Sludge-amended soils showed also the emergence of resistome for all tested antibiotics compared to non-treated controls. In this regard, the increase of sludge dose generally correlated with ARB counts, while soil texture had no influence. On the other hand, the multi-antibiotic resistance (MAR) of 52 isolates selected from USS and different soil treatments was investigated for 10 most prescribed antibiotics. Nine isolates showed significant MAR index (≥ 0.3) and co-resistance to Cd, As and Be as well. However, events including an extreme flash flood and the termination of USS applications significantly disrupted ARB communities in all soil treatments. In any case, this study highlighted the risks of ARB spread in sludge-amended soils and a greater concern with the recent exacerbation of antibiotic overuse following COVID-19 outbreak.

Assessment of coral-reef ecosystem services in West Buleleng Conservation Zone, Bali, Indonesia - Rainey Windayati; Bachtiar W. Mutaqin; Muh Aris Marfai; Evita Hanie Pangaribowo; Muhammad Helmi; Moh. Gamal Rindarjono (Journal of Coastal Conservation, 2022)

Desertification prediction with an integrated 3D convolutional neural network and cellular automata in Al-Muthanna, Iraq - Yasir Abdulameer Nayyef Aldabbagh; Helmi Zulhaidi Mohd Shafri; Shattri Mansor; Mohd Hasmadi Ismail (Environmental Monitoring and Assessment, 2022)

DeepAutoMapping: low-cost and real-time geospatial map generation method using deep learning and video streams - Jalal Ibrahim Al-Azizi; Helmi Zulhaidi Mohd Shafri; Shaiful Jahari Bin Hashim; Shattri B. Mansor (Earth Science Informatics, 2022)

Production of biodiesel from salvia mirzayanii oil via electrolysis using KOH/Clinoptilolite as catalyst - Maryam Helmi; Alireza Hemmati; Kambiz Tahvildari (Journal of Environmental Health Science and Engineering, 2022)

Biochemical Assessments of Neurotrophin-3 and Zinc Involvement in the Pathophysiology of Pediatric Febrile Seizures - Ali Helmi Bakri; Mohammed H. Hassan; Ahmed El-Abd Ahmed; Pola Rafat Halim; Samer A. El-Sawy; Montaser Mohamed Mohamed; Nagwan I. Rashwan (Biological Trace Element Research, 2022)

Hyperspectral image classification by integrating attention-based LSTM and hybrid spectral networks - Mohammed Ahmed AL-Kubaisi; Helmi Zulhaidi Mohd Shafri; Mohd Hasmadi Ismail; Mohd Johari Mohd Yusof; Shaiful Jahari Bin Hashim (International Journal of Remote Sensing, 2022)

Chemical composition of three Malaysian Horsfieldia essential oils - Wan Mohd Nuzul Hakimi Wan Salleh; Natasa Mohd Shakri; Shamsul Khamis; William N. Setzer; Muhammad Helmi Nadri (Natural Product Research, 2022)

Bioactive metabolites of hass and reed avocados targeting methicillin-resistant Staphylococcus aureus enterotoxin-like X via molecular modeling and cytotoxicity assessments - Inas Youssef Younis; Mohamed Saeed Hifnawy; Seham Salaheldin El-Hawary; Mahitab Helmi El Bishbishy; Sawsan Youssef Elateek (Natural Product Research, 2021)

Effects of combined exposure to heat and psychological stress on oxidative stress parameters of adult male rats - Faezeh Abbasi Balochkhaneh; Somayeh Farhang Dehghan; Abbas Haghparast; Mohammad Hossein Vaziri; Mehrdad Helmi Kohanehshari; Siamak Sabour (Toxicology and Environmental Health Sciences, 2021)

A Review of Bacterial Antibiotic Resistance Genes and Their Removal Strategies from Wastewater - Zainura Zainon Noor; Zainab Rabiu; Mohd. Helmi Mohd. Sani; Abdul Fatah A. Samad; Mohd. Farizal Ahmad Kamaroddin; María Florencia Perez; Julian Rafael Dib; Huma Fatima; Rajeshwari Sinha; Sunil Kumar Khare; Zainul Akmar Zakaria (Current Pollution Reports, 2021)

Environmental impact evaluation of co-products: decision-aid tool for allocation in LCA - Walid Ijassi; Helmi Ben Rejeb; Peggy Zwolinski (The International Journal of Life Cycle Assessment, 2021)

Diurnal variation of precipitation from the perspectives of precipitation amount, intensity and duration over Sumatra from rain gauge observations - Marzuki Marzuki; Krisna Suryanti; Helmi Yusnaini; Fredolin Tangang; Robi Muharsyah; Mutya Vonnisa; Dodi Devianto (International Journal of Climatology, 2021)
The characteristics of diurnal variation of precipitation in terms of amount (PA), frequency (PF), and intensity (PI) over Sumatra have been investigated using rain‐gauge data from 186 stations. Mean PA and PF show spatial variations significantly affected by the terrain elevation and stations' distance to the west coastline of Sumatra. A slightly larger PA and PF appear over the middle and western sections of the Barisan mountains, in which the mean PI is smaller in these regions. Most stations with large rainfall amount also have large rainfall frequencies, indicated by a strong correlation between PA and PF. The timing of the diurnal peak of PA, PF, and PI also has prominent regional characteristics. The cluster analysis reveals different grouping of stations with distinctive diurnal peaks. The prevailing afternoon and early‐evening peaks, that is, 1500–2000 LST, appear mostly over mountain ranges where amplitude of PA and PF tended to increase with elevation. Moreover, the amplitude of diurnal cycles tended to decrease as distance from the Sumatra's west coastline increases. On the western side of Barisan's mountain range, high amplitude of diurnal cycle prevails compared to the eastern side. We also found a strong relationship between rain event duration with diurnal cycle pattern. Generally, rain event with a long duration tended to have a peak occurring at a later time compared with those events of shorter duration. The diurnal variation of precipitation corresponds to the temporal evolution of the low‐level convergences and wind vectors, and cloud migration modulated by land‐sea breeze system.

Bacterial Reduction of Cr(VI): Operational Challenges and Feasibility - Wan Azlina Ahmad; Chidambaran Kulandaisamy Venil; Evans M. Nkhalambayausi Chirwa; Yi-Tin Wang; Mohd. Helmi Sani; Abdul Fatah A. Samad; Mohd. Farizal Ahmad Kamaroddin; Edgardo R. Donati; Maria Sofia Urbieta; Zainul Akmar Zakaria (Current Pollution Reports, 2021)

Enhanced Weight-Optimized Recurrent Neural Networks Based on Sine Cosine Algorithm for Wave Height Prediction - Alawi Alqushaibi; Said Jadid Abdulkadir; Helmi Md Rais; Qasem Al-Tashi; Mohammed G. Ragab; Hitham Alhussian (Journal of Marine Science and Engineering, 2021)
Constructing offshore and coastal structures with the highest level of stability and lowest cost, as well as the prevention of faulty risk, is the desired plan that stakeholders seek to obtain. The successful construction plans of such projects mostly rely on well-analyzed and modeled metocean data that yield high prediction accuracy for the ocean environmental conditions including waves and wind. Over the past decades, planning and designing coastal projects have been accomplished by traditional static analytic, which requires tremendous efforts and high-cost resources to validate the data and determine the transformation of metocean data conditions. Therefore, the wind plays an essential role in the oceanic atmosphere and contributes to the formation of waves. This paper proposes an enhanced weight-optimized neural network based on Sine Cosine Algorithm (SCA) to accurately predict the wave height. Three neural network models named: Long Short-Term Memory (LSTM), Vanilla Recurrent Neural Network (VRNN), and Gated Recurrent Network (GRU) are enhanced, instead of random weight initialization, SCA generates weight values that are adaptable to the nature of the data and model structure. Besides, a Grid Search (GS) is utilized to automatically find the best models’ configurations. To validate the performance of the proposed models, metocean datasets have been used. The original LSTM, VRNN, and GRU are implemented and used as benchmarking models. The results show that the optimized models outperform the original three benchmarking models in terms of mean squared error (MSE), root mean square error (RMSE), and mean absolute error (MAE).

Community-level genetic profiles of actinomycetales in long-term biowaste-amended soils - Sonia Mokni-Tlili; Inès Mehri; Manel Ghorbel; Wafa Hassen; Abdennaceur Hassen; Naceur Jedidi; Helmi Hamdi (Archives of Microbiology, 2020)

Fusion of multispectral imagery and LiDAR data for roofing materials and roofing surface conditions assessment - Masayu Norman; Helmi Zulhaidi Mohd Shafri; Shattri Mansor; Badronnisa Yusuf; Nurul Ain Wahida Mohd Radzali (International Journal of Remote Sensing, 2020)

Identification of some Egyptian leafhopper species (Hemiptera: Cicadellidae) using DNA barcoding - Azza K. Emam; Heba E. Ibrahim; Ashraf Helmi; Abdoallah Sharaf (Biologia, 2020)

Thermal structure of hot events and their possible role in maintaining the warm isothermal layer in the Western Pacific warm pool - Anindya Wirasatriya; Hiroshi Kawamura; Muhammad Helmi; Denny Nugroho Sugianto; Teruhisa Shimada; Kohtaro Hosoda; Gentur Handoyo; Yoppik Disma Girindra Putra; Magaly Koch (Ocean Dynamics, 2020)

Synthetic antiprotozoal thiazolide drug induced apoptosis in colorectal cancer cells: implications of IL-6/JAK2/STAT3 and p53/caspases-dependent signaling pathways based on molecular docking and in vitro study - Mohamed A. Tantawy; Nagla A. El-Sherbeeny; Nawal Helmi; Reem Alazragi; Neveen Salem; Samah M. Elaidy (Molecular and Cellular Biochemistry, 2020)

Fatal sulfasalazine-induced DRESS complicated by HHV-6 reactivation and hemophagocytic lymphohistiocytosis - Helmi Ammar; Abdelbaki Azouzi; Neila Fathallah; Mohamed Ahmed Boujelben; Bouraoui Ouni; Mohamed Boussarsar; Badreddine Sriha; Chaker Ben Salem (European Journal of Clinical Pharmacology, 2020)

A case for structural health monitoring (SHM) and civionics enhances the evaluation of the load carrying capacity of aging bridges - Aftab Mufti; Karim Helmi (Innovative Infrastructure Solutions, 2019)

Assessment of drinking water quality along Port Said Canal treatment plants, Suez Canal corridor, Egypt - Mohamed Helmi Geriesh; Basma Mohamed Helmy Mansour; Hanaa Farouk (Arabian Journal of Geosciences, 2019)

Mapping the spatial distribution and changes of oil palm land cover using an open source cloud-based mapping platform - Nur Shafira Nisa Shaharum; Helmi Zulhaidi Mohd Shafri; Wan Azlina Wan Ab Karim Ghani; Sheila Samsatli; Husni Mobarak Prince; Badronnisa Yusuf; Ahmed Mohamed Hamud (International Journal of Remote Sensing, 2019)

Discriminating between large-scale oil palm plantations and smallholdings on tropical peatlands using vegetation indices and supervised classification of LANDSAT-8 - Aslinda Oon; Helmi Zulhaidi Mohd Shafri; Alex Mark Lechner; Badrul Azhar (International Journal of Remote Sensing, 2019)

Young and mature oil palm tree detection and counting using convolutional neural network deep learning method - Nurulain Abd Mubin; Eiswary Nadarajoo; Helmi Zulhaidi Mohd Shafri; Alireza Hamedianfar (International Journal of Remote Sensing, 2019)

Blood lipids and pressures data of exclusive narghile smokers compared with healthy non-smokers: studies from thin to thick - Helmi BEN SAAD (Environmental Science and Pollution Research, 2019)

Change detection on land use/land cover and land surface temperature using spatiotemporal data of Landsat: a case study of Gaza Strip - Shaban R. S. Aldhshan; Helmi Zulhaidi Mohd Shafri (Arabian Journal of Geosciences, 2019)

Public kitchen menu substitutions increase organic share and school meal sustainability at equal cost - Jaakko Nuutila; Helmi Risku-Norja; Anu Arolaakso (Organic Agriculture, 2019)

Possible Metabolic Alterations among Autistic Male Children: Clinical and Biochemical Approaches - Mohammed H. Hassan; Tarek Desoky; Hala M. Sakhr; Romany H. Gabra; Ali Helmi Bakri (Journal of Molecular Neuroscience, 2019)

Satellite-borne detection of high diurnal amplitude of sea surface temperature in the seas west of the Tsugaru Strait, Japan, during Yamase wind season - Anindya Wirasatriya; Hiroshi Kawamura; Magaly Koch; Muhammad Helmi (Journal of Oceanography, 2019)

Assessing flood inundation mapping through estimated discharge using GIS and HEC-RAS model - Ernieza Suhana Mokhtar; Biswajeet Pradhan; Abd Halim Ghazali; Helmi Zulhaidi Mohd Shafri (Arabian Journal of Geosciences, 2018)

Percentage cover, biomass, distribution, and potential habitat mapping of natural macroalgae, based on high-resolution satellite data and in situ monitoring, at Libukang Island, Malasoro Bay, Indonesia - N. Setyawidati; A. H. Kaimuddin; I. P. Wati; M. Helmi; I. Widowati; N. Rossi; P. O. Liabot; V. Stiger-Pouvreau (Journal of Applied Phycology, 2018)

Artificial intelligence and regression analysis for Cd(II) ion biosorption from aqueous solution by Gossypium barbadense waste - Manal Fawzy; Mahmoud Nasr; Heba Nagy; Shacker Helmi (Environmental Science and Pollution Research, 2018)

Seasonal toxicity variation in light-textured soil amended with urban sewage sludge: interaction effect on cadmium, nickel, and phytotoxicity - Rahma Inès Zoghlami; Helmi Hamdi; Khaoula Boudabbous; Sarra Hechmi; Mohamed Naceur Khelil; Naceur Jedidi (Environmental Science and Pollution Research, 2018)

The development of spectral indices for early detection of Ganoderma disease in oil palm seedlings - Mohamad Anuar Izzuddin; Abu Seman Idris; Mohd Noor Nisfariza; Abd Aziz Nordiana; Helmi Zulhaidi Mohd Shafri; Bahrom Ezzati (International Journal of Remote Sensing, 2017)

Role of seed germination in adaptation and reproductive isolation in Arabidopsis lyrata - Tuomas Hämälä; Tiina M. Mattila; Päivi H. Leinonen; Helmi Kuittinen; Outi Savolainen (Molecular Ecology, 2017)
Seed germination is an important developmental and life history stage. Yet, the evolutionary impact of germination has mainly been studied in the context of dormancy, or for its role in reproductive isolation between species. Here, we aim to examine multiple consequences of genetic divergence on germination traits between two Arabidopsis lyrata subspecies: ssp. petraea (Eurasia) and ssp. lyrata (North America). Postdormancy germination time, a potentially adaptive trait, showed differentiation between the populations, and quantitative trait loci ( QTL ) mapping revealed that the trait variation is mainly controlled by two antagonistic loci. These QTL areas contain several candidate genes with known function in postdormancy germination in A. thaliana . The sequence variation of three genes was consistent with differential selection, and they also included fixed nonsynonymous substitutions with potential to account for the phenotypic differentiation. We further show that the divergence between the subspecies has led to a slight but significant reduction in hybrid germination proportions, indicating incipient reproductive isolation. Comparison of reciprocal F 1 and F 2 progenies suggests that Bateson–Dobzhansky–Muller incompatibilities likely act through uniparentally inherited factors. Examination of genomewide transmission ratio distortion further revealed that cytonuclear interactions cause substantial pregermination inviability in the hybrids. These results confirm that seed germination has adaptive potential beyond the dormancy stage and that hybrid seed inviability can be one of the first reproductive barriers to arise during divergence.

Comparative assessment of water surface level using different discharge prediction models - Ernieza Suhana Mokhtar; Biswajeet Pradhan; Abd Halim Ghazali; Helmi Zulhaidi Mohd Shafri (Natural Hazards, 2017)

Organic food in food policy and in public catering: lessons learned from Finland - Helmi Risku-Norja; Anne-Kristin Løes (Organic Agriculture, 2017)

Drone-based land-cover mapping using a fuzzy unordered rule induction algorithm integrated into object-based image analysis - Bahareh Kalantar; Shattri Bin Mansor; Maher Ibrahim Sameen; Biswajeet Pradhan; Helmi Z. M. Shafri (International Journal of Remote Sensing, 2017)

New semi-automated mapping of asbestos cement roofs using rule-based object-based image analysis and Taguchi optimization technique from WorldView-2 images - Mohamed Barakat A. Gibril; Helmi Z. M. Shafri; Alireza Hamedianfar (International Journal of Remote Sensing, 2017)

Optimization and maximization of hexavalent molybdenum reduction to Mo-blue by Serratia sp. strain MIE2 using response surface methodology - Mohd Izuan Effendi bin Halmi; Siti Rozaimah Sheikh Abdullah; Helmi Wasoh; Wan Lutfi Wan Johari; Mohd Shukuri bin Mohd Ali; Noor Azmi Shaharuddin; Mohd Yunus Shukor (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Genetic differentiating Aphis fabae and Aphis craccivora (Hemiptera: Sternorranycha: Aphididae) populations in Egypt using mitochondrial COI - Ashraf Helmi; Abdoallah Sharaf (Biologia, 2016)

Land transformation assessment using the integration of remote sensing and GIS techniques: a case study of Al-Anbar Province, Iraq - Mohammed A. Jasim; Helmi Zulhaidi Mohd Shafri; Alireza Hamedianfar; Maher Ibrahim Sameen (Arabian Journal of Geosciences, 2016)

Detection of Human Enteric Viruses in Freshwater from European Countries - Emilio D’Ugo; Stefania Marcheggiani; Ilaria Fioramonti; Roberto Giuseppetti; Roberto Spurio; Karim Helmi; Delphine Guillebault; Linda K. Medlin; Ivan Simeonovski; Bas Boots; Ulrich Breitenbach; Latife Koker; et al. (Food and Environmental Virology, 2016)

Selection for population‐specific adaptation shaped patterns of variation in the photoperiod pathway genes in Arabidopsis lyrata during post‐glacial colonization - Tiina M. Mattila; Esa A. Aalto; Tuomas Toivainen; Anne Niittyvuopio; Susanna Piltonen; Helmi Kuittinen; Outi Savolainen (Molecular Ecology, 2016)
Spatially varying selection can lead to population‐specific adaptation, which is often recognized at the phenotypic level; however, the genetic evidence is weaker in many groups of organisms. In plants, environmental shifts that occur due to colonization of a novel environment may require adaptive changes in the timing of growth and flowering, which are often governed by location‐specific environmental cues such as day length. We studied locally varying selection in 19 flowering time loci in nine populations of the perennial herb Arabidopsis lyrata, which has a wide but patchy distribution in temperate and boreal regions of the northern hemisphere. The populations differ in their recent population demographic and colonization histories and current environmental conditions, especially in the growing season length. We searched for population‐specific molecular signatures of directional selection by comparing a set of candidate flowering time loci with a genomic reference set within each population using multiple approaches and contrasted the patterns of different populations. The candidate loci possessed approximately 20% of the diversity of the reference loci. On average the flowering time loci had more rare alleles (a smaller Tajima's D) and an excess of highly differentiated sites relative to the reference, suggesting positive selection. The strongest signal of selection was detected in photoperiodic pathway loci in the colonizing populations of Northwestern Europe, whereas no evidence of positive selection was detected in the Central European populations. These findings emphasized the population‐specific nature of selection and suggested that photoperiodic adaptation was important during postglacial colonization of the species.

Spatial landslide hazard assessment along the Jelapang Corridor of the North-South Expressway in Malaysia using high resolution airborne LiDAR data - Norbazlan Mohd Yusof; Biswajeet Pradhan; Helmi Zulhaidi Mohd Shafri; Mustafa Neamah Jebur; Zainuddin Yusoff (Arabian Journal of Geosciences, 2015)

Total ozone column measurements using an ultraviolet multi-filter radiometer - P.I. Raptis; S. Kazadzis; K. Eleftheratos; P. Kosmopoulos; V. Amiridis; C. Helmis; C. Zerefos (International Journal of Remote Sensing, 2015)

Detailed intra-urban mapping through transferable OBIA rule sets using WorldView-2 very-high-resolution satellite images - Alireza Hamedianfar; Helmi Zulhaidi Mohd Shafri (International Journal of Remote Sensing, 2015)

A stable and accurate wavelet-based method for noise reduction from hyperspectral vegetation spectrum - Ladan Ebadi; Helmi Z. M. Shafri (Earth Science Informatics, 2015)

Erythropoietin enhances whole body lipid oxidation during prolonged exercise in humans - Corinne Caillaud; Philippe Connes; Helmi Ben Saad; Jacques Mercier (Journal of Physiology and Biochemistry, 2015)

Assessment of Trends in Extreme Precipitation Events: A Case Study in Piedmont (North-West Italy) - Helmi Saidi; Marzia Ciampittiello; Claudia Dresti; Giorgio Ghiglieri (Water Resources Management, 2015)

Spatio-temporal remotely sensed data for analysis of the shrinkage and shifting in the Al Hawizeh wetland - Yasser Ghobadi; Biswajeet Pradhan; Helmi Z. M. Shafri; Noordin bin Ahmad; Keivan Kabiri (Environmental Monitoring and Assessment, 2015)

Assessment of spatial relationship between land surface temperature and landuse/cover retrieval from multi-temporal remote sensing data in South Karkheh Sub-basin, Iran - Yasser Ghobadi; Biswajeet Pradhan; Helmi Zulhaidi Mohd Shafri; Keivan Kabiri (Arabian Journal of Geosciences, 2015)

An Integrated GIS Based Statistical Model to Compute Groundwater Vulnerability Index for Decision Maker in Agricultural Area - Aminreza Neshat; Biswajeet Pradhan; Helmi Zulhaidi Mohd Shafri (Journal of the Indian Society of Remote Sensing, 2014)

Early detection of basal stem rot disease ( Ganoderma ) in oil palms based on hyperspectral reflectance data using pattern recognition algorithms - Shohreh Liaghat; Reza Ehsani; Shattri Mansor; Helmi Z.M. Shafri; Sariah Meon; Sindhuja Sankaran; Siti H.M.N. Azam (International Journal of Remote Sensing, 2014)

Improving detailed rule-based feature extraction of urban areas from WorldView-2 image and lidar data - Alireza Hamedianfar; Helmi Zulhaidi Mohd Shafri; Shattri Mansor; Noordin Ahmad (International Journal of Remote Sensing, 2014)

Determining the ventilation and aerosol deposition rates from routine indoor-air measurements - Christos H. Halios; Costas G. Helmis; Katerina Deligianni; Sterios Vratolis; Konstantinos Eleftheriadis (Environmental Monitoring and Assessment, 2014)

A Novel Approach to Estimate Diffuse Attenuation Coefficients for QuickBird Satellite Images: A Case Study at Kish Island, the Persian Gulf - Keivan Kabiri; Biswajeet Pradhan; Helmi Zulhaidi Mohd Shafri; Shattri Bin Mansor; Kaveh Samimi-Namin (Journal of the Indian Society of Remote Sensing, 2013)

Investigating the Summertime Low-Level Jet Over the East Coast of the U.S.A.: A Case Study - C. G. Helmis; Q. Wang; G. Sgouros; S. Wang; Ch. Halios (Boundary-Layer Meteorology, 2013)

The climatic characteristics of extreme precipitations for short-term intervals in the watershed of Lake Maggiore - Helmi Saidi; Marzia Ciampittiello; Claudia Dresti; Giorgio Ghiglieri (Theoretical and Applied Climatology, 2013)

Quantification of Environmental Tobacco Smoke Contribution on Outdoor Particulate Aliphatic and Polycyclic Aromatic Hydrocarbons - M. Gini; M. Lianou; M. C. Chalbot; A. Kotronarou; I. G. Kavouras; C. G. Helmis (Archives of Environmental Contamination and Toxicology, 2013)

Acetone–Butanol–Ethanol Production by Clostridium acetobutylicum ATCC 824 Using Sago Pith Residues Hydrolysate - Siren Linggang; Lai Yee Phang; Helmi Wasoh; Suraini Abd-Aziz (BioEnergy Research, 2013)

A Comparative Study and Evaluation of Mixing-Height Estimation Based on Sodar-RASS, Ceilometer Data and Numerical Model Simulations - C. G. Helmis; G. Sgouros; M. Tombrou; K. Schäfer; C. Münkel; E. Bossioli; A. Dandou (Boundary-Layer Meteorology, 2012)

On the variability of the surface environment response to synoptic forcing over complex terrain: a multivariate data analysis approach - Christos H. Halios; Costas G. Helmis; Helena A. Flocas; Stephan Nyeki; Dimosthenis N. Assimakopoulos (Meteorology and Atmospheric Physics, 2012)

Detection of stressed oil palms from an airborne sensor using optimized spectral indices - Helmi Zulhaidi M. Shafri; Nasrulhapiza Hamdan; Mohamad Izzuddin Anuar (International Journal of Remote Sensing, 2012)

Development and application of an algorithm for the estimation of mixing height with the use of a SODAR-RASS remote sensing system - G. Sgouros; C. G. Helmis; J. Degleris (International Journal of Remote Sensing, 2011)

Spectral discrimination of healthy and Ganoderma -infected oil palms from hyperspectral data - Helmi Z. M. Shafri; Mohd I. Anuar; Idris A. Seman; Nisfariza M. Noor (International Journal of Remote Sensing, 2011)

Two-year monitoring of Cryptosporidium parvum and Giardia lamblia occurrence in a recreational and drinking water reservoir using standard microscopic and molecular biology techniques - Karim Helmi; Sylvain Skraber; Jean-Baptiste Burnet; Laurence Leblanc; Lucien Hoffmann; Henry-Michel Cauchie (Environmental Monitoring and Assessment, 2011)

PFR model and GiT for landslide susceptibility mapping: a case study from Central Alborz, Iran - Mehrnoosh Jadda; Helmi Z. M. Shafri; Shattri B. Mansor (Natural Hazards, 2011)

Semi-automatic detection and counting of oil palm trees from high spatial resolution airborne imagery - Helmi Z. M. Shafri; Nasrulhapiza Hamdan; M. Iqbal Saripan (International Journal of Remote Sensing, 2011)

PM1 and PM2.5 ionic composition and VOCs measurements in two typical apartments in Athens, Greece: investigation of smoking contribution to indoor air concentrations - Dikaia E. Saraga; Thomas Maggos; Constantinos G. Helmis; John Michopoulos; John G. Bartzis; Christos Vasilakos (Environmental Monitoring and Assessment, 2010)

Temporal evolution of the main processes that control indoor pollution in an office microenvironment: a case study - Christos H. Halios; Costas G. Helmis (Environmental Monitoring and Assessment, 2010)

A review on hyperspectral remote sensing for homogeneous and heterogeneous forest biodiversity assessment - Azadeh Ghiyamat; Helmi Z. M. Shafri (International Journal of Remote Sensing, 2010)

A Comparative Study of the Main Mechanisms Controlling Indoor Air Pollution in Residential Flats - Christos C. Halios; Costas G. Helmis; Kostas Eleftheriadis; Helena A. Flocas; Vasiliki D. Assimakopoulos (Water, Air, & Soil Pollution, 2009)

Low-level jet development and the interaction of different scale physical processes - G. Sgouros; C. G. Helmis (Meteorology and Atmospheric Physics, 2009)

Simultaneous Concentration of Enteric Viruses and Protozoan Parasites: A Protocol Based on Tangential Flow Filtration and Adapted to Large Volumes of Surface and Drinking Waters - Skraber Sylvain; Gantzer Christophe; Helmi Karim; Hoffmann Lucien; Cauchie Henry-Michel (Food and Environmental Virology, 2009)

PM2.5 and volatile organic compounds (VOCs) in ambient air: a focus on the effect of meteorology - A. Giakoumi; TH. Maggos; J. Michopoulos; C. Helmis; CH. Vasilakos (Environmental Monitoring and Assessment, 2009)

The Odd–Even Behaviour of Dicarboxylic Acids Solubility in the Atmospheric Aerosols - Mohd Zul Helmi Rozaini; Peter Brimblecombe (Water, Air, & Soil Pollution, 2009)

Synoptic and local scale atmospheric circulation associated with air pollution episodes in an urban Mediterranean area - H. Flocas; A. Kelessis; C. Helmis; M. Petrakakis; M. Zoumakis; K. Pappas (Theoretical and Applied Climatology, 2009)

Indoor air quality assessment in the air traffic control tower of the Athens Airport, Greece - Costas G. Helmis; Vasiliki D. Assimakopoulos; Helena A. Flocas; Ourania I. Stathopoulou; George Sgouros; Maria Hatzaki (Environmental Monitoring and Assessment, 2009)

On the Temporal Distribution of Bursts and Events in the Stable Marine Atmospheric Surface Layer - George D. Katsouvas; Costas G. Helmis (Boundary-Layer Meteorology, 2008)

Quadrant analysis of the scalar and momentum fluxes in the stable marine atmospheric surface layer - George D. Katsouvas; Costas G. Helmis; Qing Wang (Boundary-Layer Meteorology, 2007)

Model evaluation of the atmospheric boundary layer and mixed-layer evolution - Maria Tombrou; Aggeliki Dandou; Costas Helmis; Evaggelos Akylas; George Angelopoulos; Helena Flocas; Vasiliki Assimakopoulos; Nikolaos Soulakellis (Boundary-Layer Meteorology, 2007)

Temporal determination of heavy metals in PM2.5 aerosols in a suburban site of Athens, Greece - Chirstos Vasilakos; Stella Pateraki; Dimitrios Veros; Thomas Maggos; John Michopoulos; Dikaia Saraga; Costas G. Helmis (Journal of Atmospheric Chemistry, 2007)

Studying genetics of adaptive variation in model organisms: flowering time variation in Arabidopsis lyrata - Mona Riihimki; Robert Podolsky; Helmi Kuittinen; Hans Koelewijn; Outi Savolainen (Genetica, 2005)

Aerobic determinants of the decline in preferred walking speed in healthy, active 65- and 80-year-olds - Davide Malatesta; David Simar; Yves Dauvilliers; Robin Candau; Helmi Ben Saad; Christian Préfaut; Corinne Caillaud (Pflügers Archiv - European Journal of Physiology, 2004)

Evaluation of Sodar methods for the determination of the atmospheric boundary layer mixing height - D. N. Asimakopoulos; C. G. Helmis; J. Michopoulos (Meteorology and Atmospheric Physics, 2004)

Auxin distribution in Lotus japonicus during root nodule development - Cristina Pacios-Bras; Helmi R.M. Schlaman; Kees Boot; Pieter Admiraal; Julio Mateos Langerak; Jens Stougaard; Herman P. Spaink (Plant Molecular Biology, 2003)

Estimation of transboundary air pollution on the basis of synoptic‐scale weather types - C. G. Helmis; N. Moussiopoulos; H. A. Flocas; P. Sahm; V. D. Assimakopoulos; C. Naneris; P. Maheras (International Journal of Climatology, 2003)
A methodology to estimate annual transboundary atmospheric transport is proposed, taking into account different background meteorological conditions. For this purpose, the 850 hPa synoptic‐scale atmospheric circulation over the area examined was classified on a daily basis into 14 distinct synoptic types, using a database for an extended period of 40 years. The corresponding frequency of appearance of the synoptic types for a normal year was calculated. For selected days representing the synoptic types during this year, the inflow–outflow fluxes of NO x and SO 2 were estimated through a balancing box with the aid of a MEMO/TRAPPA modelling system. According to the proposed method, the total inflow–outflow fluxes were calculated using the lateral fluxes for each representative day, being weighted by the annual relative frequency of appearance of the synoptic scale weather types. It was demonstrated that this approach provides similar results to the intensive method based on day‐by‐day calculations. Furthermore, this approach is easier to use, since it is based on the simulations of selected days, and it allows the investigation of the influence of different types of atmospheric circulation on the inflow–outflow budget. Copyright © 2003 Royal Meteorological Society

Mutants in the nodFEL promoter of Rhizobium leguminosarum bv. viciae reveal a role of individual nucleotides in transcriptional activation and protein binding - Robert J.H. Okker; Herman P. Spaink; Ben J.J. Lugtenberg; Helmi R.M. Schlaman (Archives of Microbiology, 2001)

Determination of Polycyclic Aromatic Hydrocarbons in Wastewater, Sediments, Sludge and Plants in Karak Province, Jordan - Anwar Jiries; Helmi Hussain; Jutta Lintelmann (Water, Air, & Soil Pollution, 2000)

Evening and Morning Transition of Katabatic Flows - K. H. Papadopoulos; C. G. Helmis (Boundary-Layer Meteorology, 1999)

Inland Propagation of Sea Breeze under Opposing Offshore Wind - D. N. Asimakopoulos; C. G. Helmis; K. H. Papadopoulos; J. A. Kalogiros; P. Kassomenos; M. Petrakis (Meteorology and Atmospheric Physics, 1999)

Estimation of abl Parameters Using the Vertical Velocity Measurements of an Acoustic Sounder - J. A. Kalogiros; C. G. Helmis; D. N. Asimakopoulos; P. G. Papageorgas (Boundary-Layer Meteorology, 1999)

Fusions between green fluorescent protein and β-glucuronidase as sensitive and vital bifunctional reporters in plants - Nicolette E.M. Quaedvlieg; Helmi R.M. Schlaman; Pieter C. Admiraal; Susan E. Wijting; Jens Stougaard; Herman P. Spaink (Plant Molecular Biology, 1998)

Fusions between green fluorescent protein and β-glucuronidase as sensitive and vital and vital bifunctional reporters in plants - Nicolette E.M. Quaedflieg; Helmi R.M. Schlaman; Pieter C. Admiraal; Susan E. Wijting; Jens Stougaard; Herman P. Spaink (Plant Molecular Biology, 1998)

Fusions between green fluorescent protein and β-glucuronidase as sensitive and vital bifunctional reporters in plants - Nicolette E.M. Quaedvlieg; Helmi R.M. Schlaman; Pieter C. Admiraal; Susan E. Wijting; Jens Stougaard; Herman P. Spaink (Plant Molecular Biology, 1998)

Mean Characteristics of the Katabatic Flow of a 1024 m High Knife Edge Mountain - H. A. Flocas; C. G. Helmis; S. N. Blikas; D. N. Asimakopoulos; D. G. Deligiorgi; J. G. Bartzis (Theoretical and Applied Climatology, 1998)

Effects of Organophosphorus, Carbamate, Pyrethroid and Organochlorine Pesticides, and a Heavy Metal on Survival and Cholinesterase Activity of Chironomus riparius Meigen - H. Ibrahim; R. Kheir; S. Helmi; J. Lewis; M. Crane (Bulletin of Environmental Contamination and Toxicology, 1998)